2019
DOI: 10.1016/j.diabres.2019.107807
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HbA1c levels and body mass index for prevention of diabetic kidney disease: A retrospective longitudinal study using outpatient clinical data in Japanese patients with type 2 diabetes mellitus

Abstract: This study examined the association among the onset of diabetic kidney disease (DKD), blood glucose levels (HbA1 C ), and body mass index (BMI) in Japanese patients with type 2 diabetes mellitus. Methods: Patients eligible for this study included those with type 2 diabetes who visited the outpatient clinic at Kawasaki Medical School Hospital between 2000 and 2018 and were followed up for more than two years. The Cox proportional hazards model was used in four categories of subjects: at the beginning of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…Insulin resistance as a clinical characteristic of T2DM is closely related to obesity. Improving insulin resistance is one of the major targets in diabetes treatment [32][33][34] . However, studies focusing on the role of KD in the improvement of insulin resistance in patients with diabetes are very limited; most of the studies focused on the effect in obese subjects 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance as a clinical characteristic of T2DM is closely related to obesity. Improving insulin resistance is one of the major targets in diabetes treatment [32][33][34] . However, studies focusing on the role of KD in the improvement of insulin resistance in patients with diabetes are very limited; most of the studies focused on the effect in obese subjects 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dyslipidaemia and renal disease work together to worsen the clinical situation of diabetics and increase the risk of renal or cardiovascular consequences ( 4 ). Body composition indicators, such as body mass index (BMI), can predict the prognosis and complications of patients with T2DM, such as diabetic nephropathy (DKD); the predictor effect being similar to that of glycated haemoglobin (HbA1c) ( 5 ). Therefore, such indicators are of importance in monitoring disease progress and evaluating the prognosis and quality of life of patients with T2DM.…”
mentioning
confidence: 99%
“…Nakanishi’s study also suggested an association between renal function and HbA1c, suggesting that HbA1c>7.0% increases the risk of diabetic microangiopathy, which increases the risk of diabetic nephropathy. 13 In our results, HbA1c was most closely related to blood glucose, so we focused on analyzing the influence of HbA1c on trauma patients. There are some studies on the relationship between blood sugar and trauma prognosis, but the results are not consistent.…”
Section: Discussionmentioning
confidence: 98%